Organoleptic Quality and Protein Content of Banana Blossom Jerky with Supplementation of Tofu Dregs - Yani, Irma Eva; Salma; Karmila, Imra Ati (proceedinginternational, 2024)
Banana blossom jerky is a vegetable-based jerky made from banana blossom and spices. Banana blossom contains complete nutrients such as carbohydrates, fat and fiber, but its protein content is low, so it is necessary to add protein-rich ingredients to increase its nutritional value, such as tofu dregs.The purpose of this study was to determine the organoleptic quality and protein content of banana blossom jerky with supplementation of tofu dregs. This type of research is an experiment using a completely randomized design (CRD), namely 3 treatments, 1 control and 2 repetitions. Observations were made in two ways, namely subjective (hedonic test/organoleptic quality) analyzed by the variance test (ANOVA) which has been continued with the DNMRT test at the 5% level and objective (protein content test) with the Kjedhal micro method. The results of the study based on the variance test (ANOVA) found that banana blossom jerky in terms of color ranged from 2.84-3.02 (like), aroma ranged from 3.06-3.16 (like), taste ranged from 2.58-3.02 (like), and texture ranged from 2.52-3.04 (like). The results of this study show that the average acceptance is at the level of like and the best treatment in banana blossom jerky with supplementation of tofu dregs is treatment C with the addition of 40 grams of tofu dregs with a protein content of 3.92%. After the variance analysis test (ANOVA), there was a significant difference in terms of taste and texture of the added tofu dregs. Further research is recommended to examine the shelf life/durability of banana heart jerky with the addition of tofu dregs